Execução orçamentária e políticas de financiamento do Instituto Federal de Educação, Ciência e Tecnologia da Paraíba: 2016-2021 - Almeida, Maria das Graças Moreira de (2023)
This research presents an analysis of the budget execution and sources of financing of the Federal Institute of Paraíba (IFPB) in the context of austerity policies, control, and reduction of public spending, from 2016 to 2021. The objectives of the investigation include: a) characterizing the financing of Federal Institutes and the possible effects of austerity policies on them; b) describing the budget profile of IFPB; c) understanding the relationships between IFPB revenue performance and sources of financing; d) developing an informative E-book for all IFPB employees on the institution's budget execution process. To achieve these objectives, a documentary survey was conducted on managerial treasury spreadsheets, SIOP (Integrated System of Planning and Budgeting of the Federal Government) spreadsheets, SIAFI (Integrated Financial Administration System of the Federal Government) reports, and management reports. In addition, data related to government actions aimed at financing Federal Institutes and the process of implementing and developing the Program for Support to Plans for Restructuring and Expansion of Federal Universities (REUNI) were analyzed. During the analyzed period, IFPB went from 9 to 21 campuses, and there was an expansion of the budget. However, austerity policies and Constitutional Amendment No. 95/2016 resulted in significant budget reductions, blocking, and contingency measures. The budget reduction affected essential areas such as Investment, which had a reduction of 68%, leading to discontinuity in the institution's expansion process, as well as the deterioration of laboratories and the physical structure of the campuses. Other Current Expenses had a reduction of 20%, leading the institution to carry out operational maneuvers to maintain the precarious operation of units and fulfill commitments. Resources allocated to Student Assistance had a reduction of 17%, while the number of students increased by 79.07%, compromising the students' retention in the institution, especially those with low income.